Cadmium accumulation characteristics of floricultural plant Cosmos bipinnata*. Issue 9 (21st October 2017) - Huang, Jiajing; Yang, Zhanbiao; Li, Jianhua; Liao, Ming'an; Lin, Lijin; Wang, Jin; Yang, Yuanxiang; Liang, Dong; Xia, Hui; Wang, Xun; Ren, Wei
ABSTRACT: The artificially high soil cadmium (Cd) concentration screening method was used to screen Cd-hyperaccumulators from floricultural plants. Among the five species of floricultural plants screened, Cosmos bipinnata showed the characteristics of Cd-accumulators. A pot experiment was conducted to further study Cd accumulation characteristics of C. bipinnata . The results showed that the biomass, chlorophyll content, superoxide dismutase activity, peroxidase activity and soluble protein content of C. bipinnata first increased and later decreased with the increase in soil Cd concentration, but the carotenoid content and catalase activity of C. bipinnata reduced. Cd contents in roots, stems, leaves and shoots of C. bipinnata increased with increasing soil Cd concentration. When the soil Cd concentration was 50 mg kg −1, the Cd content in shoots was up to 112.62 mg kg −1, which was higher than the Cd-hyperaccumulator critical value. The root and shoot bioconcentration factors exceeded 1 in various Cd treatments, but the translocation factors were less than 1. When the soil Cd concentration was 50 mg kg −1, the Cd accumulation in shoots achieved the maximum of 224.30 μg plant −1 . Therefore, considering the tolerance and accumulation of Cd, C. bipinnata is a Cd-accumulator that could be used to remediate Cd-contaminated urban soil.